Location Based Web Service for Solving Common Locality Issues - Manisha Nair, Laasya Priya Reddy Nellore, A.M.J. Muthu Kumaran (International Journal of Advanced Science and Technology, 2020)
In these days, services based on location are being immensely utilized and this includes identifying different user/client locations. In our project we have proposed a location based web service for handling certain common problems that occur in a locality. Here, weare going to create a web service to solve a few problems like water, electricity, sewage, etc. in a particular area which depends on the user’s location. Once we file complaints in the website, it will be moved on to the particular department. The department will view our complaints and later respond to them. Once the problem is solved the information will be put on the web service which can be accessed by the users. In addition, the users will also be able to view the status of their complaints at regular intervals of time. We have proposed safety and encryption algorithms to ensure that user’s data is safeguarded by all means. Hence, we enable residents to get an easy solution to their locality issues by acting as an intermediate between them and the various departments.